Descarte inadequado de resíduos sólidos na orla de Tucuruí-PA - MOTA, Luiza Benelice Salomão (2025)
This research focuses on the improper disposal of solid waste in section 3 of the newly renovated Tucuruí lake waterfront in Pará, Brazil, which attracts a significant number of visitors, especially on weekends. Despite the availability of trash bins, incorrect waste disposal has increased with rising foot traffic, adversely affecting the environment, public health, and local sanitation. Interviews with 35 individuals revealed uncertainty about garbage collection frequency, with 86.4% expressing doubts, indicating communication failures. Although 82.9% deemed the number of bins adequate, poor distribution poses a problem. The main reasons for improper disposal are carelessness (48.6%) and lack of awareness (37.1%), underscoring the urgency for environmental education. Plastic waste is the most common, reflecting the global pollution issue. Therefore, it is essential to implement educational campaigns, encourage recycling, and reduce plastic use, supported by integrated public policies to enhance solid waste management in the Tucuruí waterfront.